2000
DOI: 10.1271/bbb.64.2559
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Alkaloids and Related Compounds Produced by the FungusPenicilliumcf.simplicissimum

Abstract: A new nematicidal alkaloid, peniprequinolone (1), together with the known alkaloids penigequinolones A and B (2a, 2b), 3-methoxy-4-hydroxy-4-(4'-methoxyphenyl)quinolinone (3), and 3-methoxy-4,6-dihydroxy-4-(4'-methoxyphenyl)quinolinone (4), were isolated from Penicillium cf. simplicissimum (Oudemans) Thom. Cyclopenin (5) and a compound (6a/6b) structurally related to cyclopenin also were isolated from the fungus, and their structures were established by spectroscopic analysis. The biological activities of 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 23 publications
5
74
0
1
Order By: Relevance
“…NOE experiments for 3 to 7 showed similar results to those for 2, indicating that the stereochemistry of their quinolinone skeleton is 3R*, 4R*. Biosynthetic studies of this series of compounds have not been reported so far, but the biosynthetic pathway could be speculated to be as follows [5]. First, diketodiazepins 15 and 16 are biosynthesized from anthranilic acid and tyrosine, which are de-and re-cyclized to form the fundamental phenylquinolinones (1, 2, 10 and 11).…”
Section: Relative Stereochemistry Of P-methoxyphenyl Quinolinone Skelmentioning
confidence: 58%
See 1 more Smart Citation
“…NOE experiments for 3 to 7 showed similar results to those for 2, indicating that the stereochemistry of their quinolinone skeleton is 3R*, 4R*. Biosynthetic studies of this series of compounds have not been reported so far, but the biosynthetic pathway could be speculated to be as follows [5]. First, diketodiazepins 15 and 16 are biosynthesized from anthranilic acid and tyrosine, which are de-and re-cyclized to form the fundamental phenylquinolinones (1, 2, 10 and 11).…”
Section: Relative Stereochemistry Of P-methoxyphenyl Quinolinone Skelmentioning
confidence: 58%
“…1 H and 13 C NMR data of 13 and 14 are also shown for comparison. From the MS, 1 H and 13 C NMR (data not shown), 10 to 16 were identified as 4-hydroxy-3,4-dihydro-3-methoxy-4-(4Ј-methoxyphenyl)-2(1H)-quinolinone (quinolinone A, 10) [4], 4,5-dihydroxy-3,4-dihydro-3-methoxy-4-(4Ј-methoxyphenyl)-2(1H)-quinolinone (quinolinone B, 11) [4], peniprequinolone (12) [5], penigequinolones A and B (13, 14) [5,6], 4Ј-methoxycyclopeptin (15) [5] and transdehydro-4Ј-methoxycyclopeptin (16) [7]. Compounds 1 and 2 were named yaequinolones A1 and A2 in this study, therefore these structural elucidations were described blow.…”
Section: Structural Elucidationmentioning
confidence: 99%
“…4-Hydroxy-3,4-dihydro-3-methoxy-4-(4Ј-methoxyphenyl)-2(1H)-quinolinone (abbreviated quinolinone A in this study) (10) [10] and 4,5-dihydroxy-3,4-dihydro-3-methoxy-4-(4Ј-methoxyphenyl)-2(1H)-quinolinone (quinolinone B) (11) [10], were originally isolated as insecticidal antibiotics against A. salina from Penicillium simplicissimum. Peniprequinolone (12) [11] was isolated as a nematicidal antibiotic against root-lesion nematode Pratylenchus penetras from Penicillium cf. simplicissimum.…”
Section: Introductionmentioning
confidence: 99%
“…simplicissimum. Penigequinolones A and B (13, 14) [11,12], isolated as a mixture from Penicillium sp. NO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation